2006
DOI: 10.1002/biot.200500051
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing of recombinant therapeutic proteins in microbial systems

Abstract: Recombinant therapeutic proteins have gained enormous importance for clinical applications. The first recombinant products have been produced in E. coli more than 20 years ago. Although with the advent of antibody-based therapeutics mammalian expression systems have experienced a major boost, microbial expression systems continue to be widely used in industry. Their intrinsic advantages, such as rapid growth, high yields and ease of manipulation, make them the premier choice for expression of non-glycosylated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
1
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(103 citation statements)
references
References 294 publications
0
95
1
6
Order By: Relevance
“…Culture Growth Parameters. Dissolved oxygen (DO) or partial oxygen pressure, pH, and temperature are among the most relevant physiological parameters for a fermentation process (Cereghino et al, 2002;Graumann and Premstaller, 2006). This study characterizes their effect on growth kinetics during the batch and fed-batch growth phases of the fermentation process.…”
Section: Resultsmentioning
confidence: 99%
“…Culture Growth Parameters. Dissolved oxygen (DO) or partial oxygen pressure, pH, and temperature are among the most relevant physiological parameters for a fermentation process (Cereghino et al, 2002;Graumann and Premstaller, 2006). This study characterizes their effect on growth kinetics during the batch and fed-batch growth phases of the fermentation process.…”
Section: Resultsmentioning
confidence: 99%
“…Escherichia coli and yeast are among the most widely used systems for the production of recombinant proteins (22)(23)(24), and bioinformatics has facilitated the production of a variety of recombinant proteins that have been investigated as Leishmania vaccine antigen candidates in animal models (15,20). Key to the use of recombinant proteins is the cost-effectiveness of production, an important consideration when modeling has shown that a cost of $2 or less per dose for a preventive vaccine would be economically advantageous over the currently available leishmaniasis treatments (25).…”
Section: Purified Recombinant Proteinsmentioning
confidence: 99%
“…Plants can be used as bioreactors for large scale production of therapeutic antibodies at a low cost [40,41]. Significant progress has been made in the expression of mAbs in plants.…”
Section: Manufacturing Costmentioning
confidence: 99%